2014
DOI: 10.1371/journal.pone.0109685
|View full text |Cite
|
Sign up to set email alerts
|

Health Risk Assessment for Air Pollutants: Alterations in Lung and Cardiac Gene Expression in Mice Exposed to Milano Winter Fine Particulate Matter (PM2.5)

Abstract: Oxidative stress, pulmonary and systemic inflammation, endothelial cell dysfunction, atherosclerosis and cardiac autonomic dysfunction have been linked to urban particulate matter exposure. The chemical composition of airborne pollutants in Milano is similar to those of other European cities though with a higher PM2.5 fraction. Milano winter fine particles (PM2.5win) are characterized by the presence of nitrate, organic carbon fraction, with high amount of polycyclic aromatic hydrocarbons and elements such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
47
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(56 citation statements)
references
References 71 publications
8
47
0
1
Order By: Relevance
“…Genes spanning all three gene clusters from this analysis including TLR8 , COL11A1 , and LTBP3 ( Figure 5C ) were previously associated in other studies ranging from smoking, ozone, particulate matter, asthma, and chronic obstructive pulmonary disease (Konigshoff, Kneidinger et al 2009, Shi, Chen et al 2009, Bauer, Diaz-Sanchez et al 2012, Bezemer, Sagar et al 2012, Sancini, Farina et al 2014). The identification of extracellular signaling molecules within each cluster suggest a dynamic role for the extracellular matrix and the regulation of secretory molecules in response to diesel exposure.…”
Section: Resultssupporting
confidence: 67%
“…Genes spanning all three gene clusters from this analysis including TLR8 , COL11A1 , and LTBP3 ( Figure 5C ) were previously associated in other studies ranging from smoking, ozone, particulate matter, asthma, and chronic obstructive pulmonary disease (Konigshoff, Kneidinger et al 2009, Shi, Chen et al 2009, Bauer, Diaz-Sanchez et al 2012, Bezemer, Sagar et al 2012, Sancini, Farina et al 2014). The identification of extracellular signaling molecules within each cluster suggest a dynamic role for the extracellular matrix and the regulation of secretory molecules in response to diesel exposure.…”
Section: Resultssupporting
confidence: 67%
“…In addition, PAHs are also suggested to be associated with CVD (Baxter et al, 2014). It has been reported that PM 2.5 with a small size can penetrate deeply into the alveolar regions of the lung and even transmit through blood into the circulation, including the heart, and then triggers cardiovascular effects (Guarnieri and Balmes, 2014;Sancini et al, 2014). Our data showed that PM 2.5 exposure results in lung inflammation and injury, which may further cause cardiovascular effects and then lead to cardiac injury.…”
Section: Discussionmentioning
confidence: 57%
“…The in ltration of PM in lung is known to disrupt the cell membrane integrity and subsequently increase the intracellular calcium ion (Ca 2+ ) concentration. The calcium signaling affects a broad spectrum of cellular functions such as motility, metabolism, cell growth, proliferation and apoptosis (35) and the dysregulation of intracellular Ca 2+ has been reported to associate with PM-induced oxidative stress and in ammation in human lung broblast cells (36), pulmonary artery endothelium cells (37), and mouse lungs (38). Proteins that control e ux and in ux of calcium stand important roles in calcium homeostasis.…”
Section: Discussionmentioning
confidence: 99%